Reduction of endocytosis and EGFR signaling is associated with the switch from isolated to clustered apoptosis during epithelial tissue remodeling in Drosophila. - Yuswan, K.; Sun, X.; Kuranaga, E.; Umetsu, D. (PLoS Biology, 2024)
Epithelial tissues undergo cell turnover both during development and for homeostatic maintenance. Removal of cells is coordinated with the increase in number of newly dividing cells to maintain barrier function of the tissue. In Drosophila metamorphosis, larval epidermal cells (LECs) are replaced by adult precursor cells called histoblasts. Removal of LECs must counterbalance the exponentially increasing adult histoblasts. Previous work showed that the LEC removal accelerates as endocytic activity decreases throughout all LECs. Here, we show that the acceleration is accompanied by a mode switching from isolated single-cell apoptosis to clustered ones induced by the endocytic activity reduction. We identify the epidermal growth factor receptor (EGFR) pathway via extracellular-signal regulated kinase (ERK) activity as the main components downstream of endocytic activity in LECs. The reduced ERK activity, caused by the decrease in endocytic activity, is responsible for the apoptotic mode switching. Initially, ERK is transiently activated in normal LECs surrounding a single apoptotic LEC in a ligand-dependent manner, preventing clustered cell death. Following the reduction of endocytic activity, LEC apoptosis events do not provoke these transient ERK up-regulations, resulting in the acceleration of the cell elimination rate by frequent clustered apoptosis. These findings contrasted with the common perspective that clustered apoptosis is disadvantageous. Instead, switching to clustered apoptosis is required to accommodate the growth of neighboring tissues.